(untitled) (Al-Academy, 2023)
While art presents different political representations that sometimes lead to indirect propaganda, there is another art with direct political propaganda that translates ideological perceptions with the aim of political promotion through graphic display and its influential artistic potential. This research aims to identify political propaganda representations in the contemporary graphic art. After reviewing the various theoretical opinions on the concept of propaganda and reviewing the history of art from this perspective, and after selecting and analyzing the research sample, the research concluded with a set of results and conclusions, including, that all arts are propaganda to varying degrees, and that they involve a certain goal and include a specific message or meaning, and that the political and ideological conflict produced propaganda graphic representations and produced their opposites in return.